2019
DOI: 10.1093/humrep/dez186
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte matched follicular fluid anti-Müllerian hormone is an excellent predictor of live birth after fresh single embryo transfer

Abstract: STUDY QUESTION What is the relationship between the anti-Müllerian hormone (AMH), gonadotropin and androgen concentrations within a single follicle and live birth after ICSI and a transfer of an embryo developed from the matched oocyte? SUMMARY ANSWER Among the analysed markers on the day of oocyte retrieval, AMH concentration in follicular fluid (FF) is a predictor of live birth after single embryo transfer (SET). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…Reports in humans have positively associated the presence of anti-Müllerian hormone (AMH) in FF with competence of the respective oocyte [166,167], although with some contradictory results [168,169]. Conversely, a recent study that used a large population of transferred embryos matching FF samples indicated that the AMH level in FF following withdrawal from the ovarian follicle is closely linked to the oocyte's competence, and it is a suitable predictor of a live birth after single embryo transfer [170]. In the cow, it was already reported that AMH concentrations can be predictive of the number of ovulations and embryos produced in response to ovarian stimulation by FSH [171][172][173], making it a suitable molecule to be related to the oocyte competence.…”
Section: Follicular Fluid Analysismentioning
confidence: 99%
“…Reports in humans have positively associated the presence of anti-Müllerian hormone (AMH) in FF with competence of the respective oocyte [166,167], although with some contradictory results [168,169]. Conversely, a recent study that used a large population of transferred embryos matching FF samples indicated that the AMH level in FF following withdrawal from the ovarian follicle is closely linked to the oocyte's competence, and it is a suitable predictor of a live birth after single embryo transfer [170]. In the cow, it was already reported that AMH concentrations can be predictive of the number of ovulations and embryos produced in response to ovarian stimulation by FSH [171][172][173], making it a suitable molecule to be related to the oocyte competence.…”
Section: Follicular Fluid Analysismentioning
confidence: 99%
“…There are contrasting data reported on the role of AMH in predicting embryo quality. While some studies revealed that serum AMH was not significantly associated with morphokinetic embryo quality as assessed by time-lapse imaging ( 58 , 59 ), there were reports that the oocyte-specific AMH concentration in follicular fluid had good prediction on embryonic development and live birth ( 60 , 61 ). It is interesting to further explore the functional relationship of follicular and serum AMH with oocyte competence, embryo euploidy and its role in embryo selection.…”
Section: Initial Observationsmentioning
confidence: 99%
“… 29 However, Ciepiela believed that there was a positive correlation between oocyte matched AMH levels in follicular fluids and the live birth rate after fresh single embryo transfer. 30 We hypothesized that the positive effect of CHM on the outcomes of PCOS patients undergone IVF may have relationship to the decrease of AMH levels in follicular fluids. However, the downstream molecular mechanism needs further study.…”
Section: Discussionmentioning
confidence: 99%